Internal Fixation with a Veterinary Cuttable Plate in Small Animals - Brüse, Sabine; Dee, J.; Prieur, W. D. (Veterinary and Comparative Orthopaedics and Traumatology, 1989)
63 cases (42 cats, 21 dogs) were treated with a newly developed plate that can be cut during surgery to the required length and may be sandwiched if one plate is not rigid enough. The plate is manufactured in lengths of 30 cm and in two different thicknesses, 1.0 mm and 1.5 mm. The thinner plate is used with 1.5 mm or 2.0 mm Cortex screws and the thicker one with 2.0 or 2.7 mm Cortex screws. Healing was generally uneventful with the exceptions noted.
Keywords: Dog; Cat; Fracture; Bone Plate